Electromyographic analysis of the oral phase of swallowing in subjects with and without atypical swallowing: A case‐control study - Begnoni, Giacomo; Cadenas de Llano‐Pérula, Maria; Willems, Guy; Pellegrini, Gaia; Musto, Federica; Dellavia, Claudia (Journal of oral rehabilitation, 2019)
Background Swallowing is a complex physiologic function developing mostly in the first years of life. After 6 years old, if mature deglutition is not achieved, swallowing persists as “atypical swallowing” (AS). Objective The aim of this study was to detect any electromyographical differences in the muscular activation pattern in patients with and without AS. Materials and methods 38 adolescents and young adults were selected for this study: 20 with atypical swallowing (AS group) and 18 without (C group). Standardised surface electromyographic analysis was performed by the same operator to detect the activity of masseter (MM), temporalis (TA) and submental (SM) muscles. A Student t test for unpaired data was carried out to detect differences between the AS and C groups. A 1‐way ANOVA was performed to detect any differences between the three couples of muscles. Results When compared to controls, AS patients showed a significantly longer duration of activity for each couple of muscles and for the whole duration of swallowing act (P < 0.0001) as well as lower intensity of the SM activity (P < 0.05) than controls. Within the AS and C groups, masticatory muscles (MM and TA) showed lower duration of activation (P < 0.01) and lower intensity of the spike (P < 0.0001) than SM. Within the C group, masticatory muscles also reached their activation spike earlier (1‐way ANOVA, P < 0.01) than SM. Conclusion Two different muscular performance models have been defined: patients with AS showed a longer activity of all the muscles involved with a lower intensity of SM activity than that of controls.